Competing risk analysis of factors related to long-term incidence of CHD. Issue 1 (18th July 2016) - MacKenzie, Gilbert; Greig, Mary; Hay, Iris; Pemberton, John
Abstract : Background: The 5-year follow-up results for the 1202 middle-aged men prospective study of coronary heart disease (CHD) incidence were published in 1980. This paper extends the follow-up, relating the development of CHD to 10 risk factors. Methods: The population studied comprised all men born in the 10-year period 1909–1918 aged 45–64 years at baseline who were registered in 6 group practices in Belfast. Some 1202 CHD-free men entered the study. Study end points included: (a) the development of CHD, (b) the development of myocardial infarction, (c) the development of angina pectoris, (d) death from myocardial infarction and (e) death from other causes. The men were followed for an average of 6.9 years, and the influence of 10 risk factors was assessed by Cox's proportional hazards model in a competing risk framework. Results: The analysis of first major CHD event identified four risk factors—diastolic blood pressure, serum cholesterol, T wave abnormality and tobacco index. First myocardial infarction depended on diastolic blood pressure, ST abnormality and tobacco index, while time to first angina pectoris depended on serum cholesterol, T abnormality, tobacco index and age at entry. These findings do not support the hypothesis of a common risk factor profile in the myocardial infarction and angina pectoris groups. The sensitivity of all models was poor. Discussion: The study confirms the role of known risk factors in the development of first CHD event. It also suggests that the risk factors involved in developing myocardial infarction and angina pectoris differ. The poor sensitivity of models suggests the presence of unmeasured risk factors in the aetiology of CHD.